The oncoprotein HBXIP facilitates metastasis of hepatocellular carcinoma cells by activation of MMP15 expression - Zheng, Sen (Cancer Manag Res, 2019)
Background: Due to the high recurrence and metastasis rate, the clinical outcomes of patients with hepatocellular carcinoma (HCC) are still unsatisfactory. Hepatitis B virus X-interacting protein (HBXIP) has been reported to play crucial roles in carcinogenesis. Purpose: We aimed to reveal the functional significance and underlying mechanism of HBXIP in HCC metastasis. Methods: Cell transwell assay, in vivo metastasis model, real-time PCR, western blot analysis, luciferase reporter and chromatin immunoprecipitation assays were applied. Results: Here, we detected the HBXIP expression level and determined its clinical significance in HCC. We found that HBXIP was significantly upregulated in HCC tissues, and correlated with vascular invasion, tumor metastasis and worse prognosis of HCC patients. HBXIP enhanced cell migration and invasion in vitro, and promoted the metastasis of HCC in vivo. Furthermore, we confirmed that HBXIP increased MMP15 expression through association with proto-oncogene c-myc. Depletion of c-myc abolished HBXIP-mediated MMP-15 upregulation. We also observed a positive correlation between HBXIP and MMP15 expression in HCC tissues. Conclusion: Our results establish a novel function for HBXIP-MMP15 regulation in HCC metastasis and suggest its candidacy as a new prognostic biomarker and therapeutic target for HCC metastasis.